Solution-Focused Brief Therapy in Peer Support Groups: Addressing Pedagogical Burnout Among Early-Career Teachers in West Java - Arshy Prodyanatasari (Asesment : Journal Of Counseling Guidance, 2024)
Background: Pedagogical burnout is a critical challenge that threatens the quality of education and teacher retention, particularly in the Indonesian context where support systems are limited. Novice teachers are especially vulnerable during their early career years, necessitating effective and culturally responsive interventions.Objective: This study evaluated the effectiveness of Solution-Focused Brief Therapy (SFBT) integrated into peer support groups to address burnout among beginning teachers in West Java Province.Method: A quasi-experimental design was employed with 58 novice teachers (1-3 years of experience) allocated to either an experimental group receiving eight weekly sessions of SFBT peer support or a control group continuing the standard mentoring program.Findings and Implications: Significant group-time interactions were found for the experimental group on all burnout dimensions: emotional exhaustion (d = 1.85), depersonalization (d = 1.35), and personal accomplishment (d = 1.62), with improvements sustained at follow-up. Teacher self-efficacy significantly increased across instructional strategies (d = 1.28), classroom management (d = 1.15), and student engagement (d = 1.22). Qualitative analysis identified key mechanisms of change including cognitive reframing, recognition of personal resources, vicarious learning, emotional validation, and collaborative problem-solving. The program demonstrated strong cultural fit with Indonesian collectivist values and proved scalable through trained school counselors.Conclusion: Peer-group-based SFBT represents an effective, practical, and culturally responsive intervention for enhancing beginning teacher well-being and reducing burnout in the Indonesian educational context.